Modifying the size distribution of microbubble contrast agents for high‐frequency subharmonic imaging. Issue 8 (17th July 2013) - Shekhar, Himanshu; Rychak, Joshua J.; Doyley, Marvin M.
Abstract : Purpose: : Subharmonic imaging is of interest for high frequency (>10 MHz) nonlinear imaging, because it can specifically detect the response of ultrasound contrast agents (UCA). However, conventional UCA produce a weak subharmonic response at high frequencies, which limits the sensitivity of subharmonic imaging. We hypothesized that modifying the size distribution of the agent can enhance its high‐frequency subharmonic response. The overall goal of this study was to investigate size‐manipulated populations of the agent to determine the range of sizes that produce the strongest subharmonic response at high frequencies (in this case, 20 MHz). A secondary goal was to assess whether the number or the volume‐weighted size distribution better represents the efficacy of the agent for high‐frequency subharmonic imaging. Methods: : The authors created six distinct agent size distributions from the native distribution of a commercially available UCA (Targestar‐P ® ). The median (number‐weighted) diameter of the native agent was 1.63 μm, while the median diameters of the size‐manipulated populations ranged from 1.35 to 2.99 μm. The authors conducted acoustic measurements with native and size‐manipulated agent populations to assess their subharmonic response to 20 MHz excitation (pulse duration 1.5 μs, pressure amplitudes 100–398 kPa). Results: : The results showed a considerable difference between the subharmonic response of the agent populations that were investigated. The subharmonic response peaked for the agent population with a median diameter of 2.15 μm, which demonstrated a subharmonic signal that was 8 dB higher than the native agent. Comparing the subharmonic response of different UCA populations indicated that microbubbles with diameters between 1.3 and 3 μm are the dominant contributors to the subharmonic response at 20 MHz. Additionally, a better correlation was observed between the subharmonic response of the agent and the number‐weighted size‐distribution ( R 2 = 0.98) than with the volume‐weighted size distribution ( R 2 = 0.53). Conclusions: : Modifying the size distribution of the agent appears to be a viable strategy to improve the sensitivity of high‐frequency subharmonic imaging. In addition, when the size distribution of the UCA has not been suitably modified, the number‐weighted size distribution is a useful parameter to accurately describe the efficacy of the agent for high‐frequency subharmonic imaging.